PENINGKATAN HASIL BELAJAR PESERTA DIDIK PADA PEMBELAJARAN TEMATIK TERPADU MENGGUNAKAN MODEL PROJECT BASED LEARNING (PJBL) BERBANTUAN APLIKASI CAPCUT DI KELAS V SDN 26 AIR TAWAR TIMUR KOTA PADANG - Fitria Cahyani; Arwin Arwin (Jurnal Ilmu Pendidikan dan Kearifan Lokal, 2023)
This study aims to describe the increase in student learning outcomes in integrated thematic learning using the Project Based Learning (PJBL) model assisted by the CapCut application in class V SDN 26 Air Tawar Timur, Padang City. The type of research used is classroom action research using qualitative and quantitative approaches carried out in 4 stages, namely planning, implementing, observing and reflecting. It was carried out in cycle II where cycle I consisted of 2 meetings and cycle II consisted of 1 meeting. The data from the research were obtained from the assessment of lesson plans, implementation processes, and learning outcomes. The subjects of this study were teachers and 26 grade V students, consisting of 14 male students and 12 female students. The results of this study indicate an increase in lesson plans for cycle I obtaining an average of 78.57%, increasing in cycle II to 92.85%. The teacher aspect of the first cycle obtained an average of 79.68%, increasing in the second cycle to 93.75%. Aspects of students in cycle I obtained an average of 74.99%, increased in cycle II to 93.75%. The learning outcomes of students in the first cycle of knowledge assessment obtained an average of 77.64, increasing in cycle II to 89.09. While the results of the skills assessment in the first cycle obtained an average of 76.00, increased in the second cycle to 90.75. Thus, it can be concluded that the Project Based Learning learning model assisted by the CapCut application can improve student learning outcomes in integrated thematic learning